Exploring the Affective Politics of Political Beauty: An Antagonistic Approach - Landau, Friederike (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
To understand the intricate interconnection between politics and affects, I examine a performance of the berlin-based artist collective Zentrum für Politische Schönheit (Center for Political Beauty, ZPS), in which artist activists staged a horseback ride to fasten a manifesto of ten theses of political beauty on the façade of the German Bundestag. Interconnecting theories of political difference (Marchart 2010), which differentiate between the ontological realm of ‘the political’ and ontic realizations of ‘politics’, and political theories of affect, I approach the affective dimensions of political difference as affective politics. Building on Bargetz’s (2014) “political grammar of feelings”, I situate the performance’s temporary institutions and interruptions of ‘politics’ and ‘the political’, as well as ‘feeling politics’ and ‘politics of feeling’ respectively, as affective encounters to experience or enact political beauty. Political beauty, in an antagonistic framework that foregrounds contingency, conflict and absence, mobilizes affects as inherently ambivalent and contentious. As a challenge to the diagnosis of an inevitable post-political condition, I discuss the potential of political beauty as affective politics to potentially re-politicize politics. Borrowing from Derrida (1994), I conduct a spectral reading of ZPS’ ten theses and carve out three analytical vignettes – beauty, vitality and longing – to conceptualize political beauty as oscillating between the desire and hope for political change, which can never be fully satisfied, and a dismissal of (political) ugliness and death. In the end, political beauty escapes a definition because it is, after all, nothing but an impossible project for politics and affects of an unknown future.